SIRT6’s function in controlling the metabolism of lipids and glucose in diabetic nephropathy - Wang, Ying; Liu, Tongtong; Cai, Yuzi; Liu, Weijing; Guo, Jing (Frontiers in Endocrinology, 2023)
Diabetic nephropathy (DN) is a complication of diabetes mellitus (DM) and the main cause of excess 16 mortality in patients with type 2 DM. The pathogenesis and progression of DN are closely associated 17 with disorders of glucose and lipid metabolism. As a member of the sirtuin family, SIRT6 has 18 deacetylation, defatty-acylation, and adenosine diphosphate-ribosylation enzyme activities as well as 19 anti-aging and anticancer activities. SIRT6 plays an important role in glucose and lipid metabolism 20 and signaling, especially in DN. SIRT6 improves glucose and lipid metabolism by controlling 21 glycolysis and gluconeogenesis, affecting insulin secretion and transmission and regulating lipid 22 decomposition, transport, and synthesis. Targeting SIRT6 may provide a new therapeutic strategy for 23 DN by improving glucose and lipid metabolism. This review elaborates on the important role of 24 SIRT6 in glucose and lipid metabolism, discusses the potential of SIRT6 as a therapeutic target to 25 improve glucose and lipid metabolism and alleviate DN occurrence and progression of DN, and 26 describes the prospects for future research.